INFLUENCE OF TILLAGE PRACTICES AND RESIDUE MANAGEMENT PRACTICES ON YIELD ATTRIBUTES AND YIELD OF MAIZE IN MAIZE-BASED CROPPING SYSTEMS UNDER SEMI-ARID TROPICS - S. NARENDER REDDY; G. PADMAJA, KUMARI ADITI, GIRISH CHANDER, P. LAXMINARAYANA, S.P. WANI (The Journal of Research, PJTSAU, 2020)
A field experiment was conducted during kharif and rabi in 2016-17 and 2017-18 at International Crops Research Institute for the Semi-arid Tropics, Patancheru, Hyderabad to study the influence of tillage practices and residue management practices on yield attributes and yield of maize in maize-based cropping systems under semi-arid tropics. The field experiment was laid out on broad-beds and furrows in a split-split design with four replications under rainfed conditions. Main plot consisted of two tillage practices (minimum tillage and conventional tillage), sub-plot of two crop residue management practices (residue addition and no-residue addition) and sub-sub plot of two cropping systems (Maize-chickpea sequential cropping and maize+pigeonpea intercropping system). The results revealed that yield and yield attributes of maize did not vary significantly due to tillage practices, however, minimum tillage led to considerable yield losses. Among the residue management practices, addition of crop residue recorded significantly higher yield and yield attributes (cob girth, number of grain rows and test weight) as compared to no residue addition. Yield attributes and yield remained non-significant among the two cropping systems.